What drives youth's intention to migrate abroad? Evidence from international survey data - Santo Milasi (IZA Journal of Development and Migration, 2020)
Despite the bulk of international migrants being youth, little is known about the factors driving young people's migration behavior at the global level. Using the individual-level survey data from Gallup World Poll across 139 countries over the period 2010-2016, this study contributes to the literature by exploring a wide range of factors potentially shaping young people's (aged 15-34) desire, and a more concrete plan, to migrate abroad permanently. Results show that factors, such as holding post-secondary education, being unemployed, and working part-time involuntary, are increasing the desire of youth to migrate abroad as well as the probability that they turn this aspiration into a more concrete plan over the following year. Similarly, having negative expectations about the economic outlook, the number of available job opportunities, and the prospects for upward career mobility are found to increase the propensity to migrate abroad, both among unemployed and employed youth. Results also show that material deprivation may represent a significant push factor behind youth migration, although budgetary constraints may prevent youth from transforming their migration desires into actual plans in low-income countries. Moreover, findings suggest that contextual factors, such as discontent with local amenities and national governments, increase the desire of youth to migrate abroad, but they have little or no influence on the probability that these dreams are turned into more concrete plans. Finally, this study shows that while youth's and adults' migration propensities are often driven by the same motives, the influence of education and labor market-related factors on migration intentions is considerably stronger among youth than adults.
Keywords: F22; J13; O15; R23; 330; migration; intention to migrate; youth; labor market; brain drain